Analisis Proses Penyelesaian Klaim terhadap Asuransi Pengiriman Barang Melalui JNE - Popilaya, Chairi Nur Azizi; Kamilah; Hasibuan, Reni Ria Armayani (As-Syirkah: Islamic Economic & Financial Journal, 2023)
Shipping insurance is a necessity that arises because the transportation of goods and or cargo cannot be separated from the risks that cause losses. This writing aims to explain the terms of the implementation of insurance claims for freight forwarders at the transportation service company PT. JNE, the obstacles that cause the claim process to be not accepted and explain the procedure for claiming insurance for shipping goods. The data in writing this journal were obtained through interviews, documentation and literature study. Based on the results of the research, it is obtained that the requirements for submitting a claim are a claim submission letter, original receipt, receipt and photocopy of ID card. After completing the files that have been determined by JNE, the customer then makes a claim according to the procedures set by JNE, namely the customer comes to the counter where the customer is sending goods, or the nearest representative office. Then the customer must show the delivery receipt and claim request, then the officer will direct the customer to fill out the claim submission form. And lastly, the claim will be processed and disbursement will be made no later than 14 working days after the claim is submitted.